Improved 1-d thermohydraulic network modeling for cryogenic circuits coupled to CICC models of fusion magnet system. (January 2019) - Oh, Dong Keun; Oh, Sangjun
Highlights: The CryoSoft TM suite is revised on the accuracy issue of the nodal coupling scheme. The inherent error of nodal volume is corrected by the velocity imposed branch. Discarding the concept of effective volumes, the steady state model is also upgraded. Physically tight interface is introduced as a boundary scheme consistent with the characteristic components of the PDE. The compatibility to the SUPERMAGNET model is carefully established. Abstract: On the purpose to improve the performance of SuperMagnet model (http://www.htess.com/cryosoft.htm ), coupled 1-d flows at the multi-way branch is carefully explored in the context of hyperbolic PDEs. Comparing with the generic method found in other competitive tools, a minimalistic implementation of momentum-carrying nodal component is introduced to resolve the accuracy issue of the mixing volume under pressurization and momentum transfer. Then, an inventive boundary scheme of characteristic decomposition is followed as a remedy to reduce numerical troubles at the interfaces. Discussing the conformity of our approach to the general numerical framework of hyperbolic PDEs, the attained performance is described in the aspect of physical consistence and extensive applicability to the coupled solver system using the CryoSoft™ code suite.